Hilsa fisheries in India: a socio-economic analysis of fishers in deltaic Ganga region of river Hooghly - Chakraborty, Hena; DebRoy, Piyashi; Kunui, Arghya; Nandy, Saurav Kumar; Jana, Chayna; Sahoo, Amiya Kumar; Das, Basanta Kumar (Frontiers in Sustainable Food Systems, 2024)
Hilsa (Tenualosa ilisha) is a premium table fish in the eastern and some parts of the North-eastern region of India especially for the Bengali community contributing uniquely to the societal and economic significance of artisanal fisheries of the country. The major distribution of the fish species in India lies in the Bhagirathi – Hooghly component of the Ganga River system. The aim of the study was to examine if traditional Hilsa fisheries in India is sustainable as the livelihood of artisanal fishers in the light of the socio-economic conditions of Hilsa fishers in West Bengal. Structured socio-economic surveys were carried out with 402 fishermen from the upper stretch of river Hooghly to its lower stretch (300 km) in West Bengal during 2020-21. The average monthly income of the Hilsa fishers in the lower stretch of river Hooghly (Godakhali) (₹ 25,000 to 30,000 / USD 301 to 361) was higher than that in the upper stretch at Farakka (₹ 10,000 to 15,000 / USD 120 to 180). However, fish species other than Hilsa are generating significantly higher returns for 56% fishers in Hooghly district. 40% Hilsa fishers in South 24 Parganas and Murshidabad (Farakka) districts are engaged in non-fishery activities for livelihood. There are significant differences between Hilsa fishers with other fisheries as secondary occupations and those with non-fishery activities as secondary occupations in terms of socio-economic characteristics. These imply that Hilsa fisheries is profitable as a continued traditional livelihood but it alone is not sufficient enough to support the livelihood of the artisanal fishers. This indicates the threatened economic sustainability of the Hilsa fisheries sector at present. Considering the high market demand of Hilsa in the eastern and North-Eastern regions of India, and the market complexities, more significant investments need to be channelised into the Hilsa fisheries of the northern Bay of Bengal region. Such investments encompass a wholesome approach including more governmental initiatives for conservation and management.